Muslihat Yakub dalam Mendapatkan Hak Kesulungan Dari Esau - Siprianus Leu, Kornelius (Divinitas Jurnal Filsafat dan Teologi Kontekstual, 2024)
The lives of Jacob and Esau, Isaac's twin sons, were filled with tension and competition. Genesis 25:23 tells how the competition between the two was even prophesied by God himself from the time they were conceived. The rivalry between the two continued in the event of Jacob taking away the blessing and birthright from Esau through "deception". Through literature study, this research will attempt to understand the "deceptive" actions carried out by Jacob in taking over the blessing and birthright from Esau, thus making Jacob the ancestor of the Israelites. This research proves that Jacob's action of deceiving Esau was the writers' strategy to explain one of the laws followed by the Israelites, namely the law of retribution. Jacob who "cheated" would receive the same treatment, namely from Laban, his uncle and father-in-law and also by his own children in the event of the sale of Joseph by his own brother (Gen. 37:12-36).AbstrakKehidupan Yakub dan Esau, kedua putra kembar Ishak diwarnai dengan ketegangan dan persaingan. Kejadian 25:23 mengisahkan bagaimana persaingan antara keduanya bahkan telah dinubuatkan oleh Allah sendiri sejak keduanya dikandung. Persaingan keduanya berlanjut pada peristiwa perampasan berkat dan hak kesulungan oleh Yakub dari Esau lewat “penipuan”. Melalui studi kepustakaan, penelitian ini akan berusaha memahami tindakan “penipuan” yang dilakukan oleh Yakub dalam mengambil alih berkat dan hak kesulungan dari Esau, hingga menjadikan Yakub sebagai leluhur Bangsa Israel. Penelitian ini membuktikan bahwa tindakan Yakub yang menipu Esau adalah strategi para penulis untuk menerangkan salah satu hukum yang dianut Bangsa Israel yakni hukum retribusi. Yakub yang “menipu” akan mendapat perlakuan yang sama yakni dari Laban, paman sekaligus ayah mertuanya dan juga oleh anak-anaknya sendiri dalam peristiwa penjualan Yusuf oleh saudaranya sendiri (Kej. 37:12-36).